Ocean Circulation on Tide-locked Lava Worlds. I. An Idealized 2D Numerical Model - Yanhong Lai; Jun Yang; Wanying Kang (The Planetary Science Journal)
A magma ocean is expected to exist on the dayside of tide-locked planets if surface temperature exceeds the melting temperature of typical crust. As highly prioritized targets for the James Webb Space Telescope, more information about the surface and atmosphere of lava planets will soon be available. In most previous studies of lava planets, the system is typically assumed to be vigorously convecting and isentropic. This implies a magma ocean depth reaching ${ \mathcal O }$ (10 ^4 –10 ^5 ) m, determined by the adiabats and melting curves. In this study, we aim to simulate ocean circulation and ocean depth on tidally locked lava worlds using an idealized 2D ( x – z ) model developed by the authors. Our simulation results show that under zero or a small internal source, the maximum zonal current speed ranges from 0.1 to 1.0 m s ^−1 and the magma ocean depth remains ${ \mathcal O }$ (100) m, being more than 100 times shallower than that predicted in a fully convecting system. We demonstrate that the ocean heat transport divergence is consistently smaller than the stellar insolation by 1–2 orders of magnitude. Consequently, the impact of ocean circulation on the thermal phase curve of tidally locked lava worlds is minimal in observations.